Homo mechanicus: “Техносповідь” Ганни Осадчук - Гаврилюк, Н. (Слово і Час, 2009)
З особливою виразністю мотив техніки звучить у літературних текстах модернізму та постмодернізму. Техніка стає одним із ключових атрибутів міста й міського способу життя, а також фактором знеособлення та відчуження. Можливий наслідок взаємодії людини й техніки моделює Ганна Осадчук у вірші “Техносповідь”. Здійснено спробу інтерпретації причин і наслідків появи нового типу людини – Homo mechanicus – у світлі ідей семіотики, враховуючи систему міфологічних, релігійних, культурних уявлень людини про себе і світ. The motifs of machine and machinery should be recognized as obvious distinctive marks of literary modernism and postmodernism. It is the machinery that becomes one of the major indications of the city and the urban way of life, since it implements the processes of depersonalisation and alienation. One of the possible consequences of the interaction between the human and the machine is formulated in Hanna Osadchuk’s poem “Technoconfession”. An accurate analysis of this poem provides for deeper insight into the origins and corollaries of homo mechanicus in the light of semiotic approach as well as for localization of this new human genus within mythological, religious, and cultural frames of reference. С особенной выразительностью мотив техники звучит в литературных текстах модернизма и постмодернизма. Техника стает одним из ключевых атрибутов города и городского образа жизни, а также фактором обезличивания и отстранения. Возможное последствие взаимодействия человека и техники моделирует Анна Осадчук в стихотворении “Техноисповедь”. Сделана попытка интерпретации причин и последствий появления нового типа человека – Homo mechanicus – в свете идей семиотики и учитывая систему мифологических, религиозных, культурных представлений человека о себе и о мире.